Catheter ablation for the treatment of persistent atrial fibrillation. (October 2009) - Knecht, Séébastien; Castro-Rodriguez, Joséé; Wright, Matthew; Tran-Ngoc, Emmanuel; Morissens, Marielle; Tatnga, Valentin; Catez, Emmanuel; Peperstraete, Bééatrice; Zaoui, Nassime; Op de Beek, Vanessa; Vivian, Gabriela Flores; Mandag, Nathalie Ngo; et al.
Atrial fibrillation (AF) is the most frequent human arrhythmia and constitutes a major socioeconomic and healthcare problem. Different studies have clearly shown the superiority of catheter ablation compared with pharmacological therapy for reducing AF burden. Catheter ablation for persistent AF targets all structures potentially contributing to initiation and maintenance of AF, and has resulted in unprecedented success in maintaining sinus rhythm in the medium term, with recovery of atrial mechanical function. Periprocedural complications may rarely occur; however, catheter ablation of persistent AF has demonstrated promising results concerning improved morbidity and quality of life, and also potential benefits in terms of mortality. Therefore, it is now included in the guidelines as a reasonable alternative to pharmacological therapy to prevent recurrent AF in symptomatic patients.